Social dimensions as resources in promoting academic well-being: the case study of the University of Foggia - Signore, Fulvio; Esposito, Ciro; Di Napoli, Immacolata; Agueli, Barbara; Ingusci, Emanuela; Mannarini, Terri; Toto, Giusi Antonia; Arcidiacono, Caterina; Fantinelli, Stefania (Frontiers in Psychology, 2024)
Recently, scholars have focused more on changes in higher education, leading to significant insights into the working lives of academics and certain related processes, such as stress or well-being. The interest in academia is also justified by the role of universities as institutions that promote health and well-being, serving as a bridge between society, the world of work, and the local community. This study aims to identify social factors that can enhance the well-being of academic workers (lecturers and technical-administrative staff), highlighting how processes linked to social identity, based on the dynamics of identification with a territory or an organization, can serve as resources that promote wellbeing. Researchers conducted the survey on 198 workers at the University of Foggia (South Italy). Correlation and reliability assessments were first performed between the variables. Finally, a SEM study was completed. The goodness of fit of the model seems to be sufficient. The social aspects examined in the study, namely, organization identification, territorial well-being, and place attachment, were positively and significantly correlated with general well-being. Findings of the study demonstrated that for teaching and technical-administrative staff, among the key components for enhancing well-being in the academic setting was the social dimension of relationships, understood both inside and outside the university. Therefore, acting the belonging process to an area, implementing and strengthening relations with the social actors involved, as well as on the sense of belonging and identification with an organization, can have precise impact in enhancing well-being.